SINTESIS LI-NMC MELALUI METODE SOLID STATE MENGGUNAKAN MHP DAN NISO4 SEBAGAI VARIASI SUMBER NIKEL - Haryadi; Iwan Ridwan; Muhammad Salman Alfarisi; Rizky Yanuar Haz (Department of Chemical Engineering, Politeknik Negeri Bandung, 2025)
Li-NMC-based cathodes are widely developed for next-generation batteries due to their high electrochemical performance and energy density. This study focuses on synthesizing Li-NMC type NMC811 using two nickel sources Mixed Hydroxide Precipitate (MHP) and nickel sulphate (NiSO4) through the solid state method. The process involved calcination at 500°C for 5 hours and sintering at 700oC, 800oC, and 900oC for 12 hours. The aim was to analyze the effect of temperature and nickel source on the crystallinity and crystal size of Li-NMC. X-Ray Diffraction (XRD) revealed that low crystallinity was observed at 700oC due to broad and weak diffraction peaks. Sintering at 800oC improved the structure and showed the presence of a Li0.88Mn2O4 phase. At 900oC, samples showed sharp peaks and high intensity, indicating excellent crystallinity. Crystal size analysis using the Debye-Scherrer equation showed that NiSO4 samples reached 41.98 nm at 800oC, while MHP samples achieved 71.69 nm at 900oC both exceeding the commercial size of 29.56 nm. These results suggest that 800-900oC is optimal for Li-NMC synthesis, and MHP is a promising alternative nickel source.